Психологічні особливості якості життя осіб з серцево-судинними захворюваннями - Магдисюк, Людмила Іванівна (Рівненський державний гуманітарний університет, 2017)
Стаття присвячена аналізу якості життя осіб пізньої зрілості з серцево-судинними захворюваннями. Вказано параметри якості життя осіб пізньої зрілості з серцево-судинними захворюваннями: задоволеність життям, відпочинок, щоденний режим, інтелектуальна і соціальна діяльність, сприйняття загального здоров’я, симптомів основного і супутніх захворювань, економічне становище, добробут, житлові умови. Запропоновано один із засобів боротьби з серцево-судинними захворюваннями є зміна мислення, направленості думок, основою яких є переживання, відчуття людини; фізичні тренування зміцнюють серцевий м’яз, судинну систему, також розвивають скелетну мускулатуру, систему дихання, що значно полегшує роботу апарату кровообігу.

The paper is devoted to the analyses of the quality of life of people with late maturity cardiovascular diseases. The parameters of quality of life of people with a late maturity cardiovascular disease: a life satisfaction, a leisure, a daily regimen, an intellectual and social activity, a perception of general health, the symptoms of general and underlying disease, an economic situation, a welfare, the housing conditions are pointed out. It is determined that the quality of life is an integral feature of psychological, physical, emotional and social functioning of person, based on his /her subjective sensation. The basic components of quality of life:psychological, social, physical and a spiritual well-being are described. There are determined the symptoms of patients with the problems of the cardiovascular system, they are: dyspnea, edema, asthenia, insomnia, a decreased physical activity, which significantly affects the overall condition, the perception of the patient and the severity of the symptoms. It is noted that cardiovascular diseases belong to a class of diseases associated with disorders of the heart or blood vessels. There are suggested the following means of the cardiovascular disease prevention: change of the way of thinking and thoughts direction, which are based on emotions, sensations; physical exercises strengthen the heart muscle, vascular system, they also develop skeletal muscles, respiratory system, that improves greatly the work of the circulatory system.
Keywords: здоров’я; якість життя; особистість; пізня зрілість; серцево-судинні захворювання; населення; психологічні особливості; психічне здоров’я; психологічне благополуччя